An urbanization monitoring dataset for world cultural heritage in the Belt and Road region. Issue 1 (2nd January 2022) - Xiao, Da; Lu, Linlin; Wang, Xinyuan; Nitivattananon, Vilas; Guo, Huadong; Hui, Wenhua
ABSTRACT: World cultural heritage refers to properties recognized as having historical, social, and anthropological value. Global urbanization has changed the land cover, land use, transportation, landscape, and local environment in cities, and thus exposed World Heritage sites to risks induced by direct or indirect damaging factors. In this paper, an urbanization intensity index (UII) was developed to quantitatively measure urban dynamics in the vicinity of World Heritage sites. This index is based on three global Earth observation datasets, including a global human settlement layer, a global population grid product, and a global nighttime light imagery. Large UII values represent high urbanization levels and intensive human activities in the study area and vice versa. The assessment results show that the mean UII value at 79 world cultural heritage sites in the Belt and Road region increased from 0.26 in 2000 to 0.29 in 2015. The heritage sites were then classified into four types based on the change rates of UIIs. A total of seven heritage sites were identified as exposed to risks due to urban sprawl and infrastructure expansion. The UII dataset can be combined with UNESCO's periodic reports and site-specific data to provide valuable information for international communities to develop heritage preservation policies. The dataset is available at http://www.dx.doi.org/10.11922/sciencedb.980 .